Komponen Pembelajaran pada Transfer Pengetahuan Pewarisan Bisnis Keluarga Industri Pandai Besi - Choiro, Umu Da'watul; Rahma, Rezka Arina (Fakultas Ilmu Pendidikan-Universitas Negeri Malang, 2023)
Blacksmithing is a life skill based on local wisdom to support people's lives. Transfer of knowledge in the blacksmith industry takes place informally through learning while working. The purpose of this study was to determine the learning components of the blacksmith's knowledge transfer. This research uses a qualitative case study approach with interview and observation methods. The learning components in the knowledge transfer of the blacksmith industry include panjak as students, masters and senior panjak as educators. The aim of learning is to produce panjaks that master a series of skills ranging from basic, intermediate, to advanced skills, as provisions for work and even the skills of trying to open their own pande. The media used are the same as the equipment and materials for the production process. Pande and the master's house as a place to study. Study time is the same as pande production time. Learning methods include nuntui, nuturi, practice and question and answer. Evaluation of learning in the learning process runs naturally through observations of panjak performance.